2006
DOI: 10.1093/aje/kwj159
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Infection with Mycobacterium avium Complex

Abstract: Infection with Mycobacterium avium complex is acquired from the environment, but risk factors for M. avium complex infection and disease are poorly understood. To identify risk factors for infection, the authors performed a 1998-2000 cross-sectional study in western Palm Beach County, Florida, using a population-based random household survey. M. avium complex infection was identified by use of the M. avium sensitin skin test. Of 447 participants, 147 (32.9%) had a positive test reaction, 186 (41.6%) had a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 27 publications
0
60
1
1
Order By: Relevance
“…The prevalence of environmental mycobacteria is also known to vary greatly with soil characteristics [159,160]. While in the USA, BCG has never been used on a large scale, in those areas in which it was used in a clinical trial, its lasting superimposed effect on test specificity can be seen, even many years after the trial.…”
Section: Test Specificitymentioning
confidence: 99%
“…The prevalence of environmental mycobacteria is also known to vary greatly with soil characteristics [159,160]. While in the USA, BCG has never been used on a large scale, in those areas in which it was used in a clinical trial, its lasting superimposed effect on test specificity can be seen, even many years after the trial.…”
Section: Test Specificitymentioning
confidence: 99%
“…Detailed descriptions of the survey methods have been previously reported (21)(22)(23). Between January 1998 and October 2000, a randomized population-based tuberculin skin test survey was performed in a rural area of western Palm Beach County, Florida.…”
Section: Community Surveymentioning
confidence: 99%
“…Some studies implicate water as the source of infection, especially in HIVinfected individuals (16,17,36). Van Coppenraet et al (50) could not find a link between pet birds and the incidence of mycobacterial lymphadenitis in children, concluding that infection can occur from any environmental source, while other authors have found a strong correlation between soil and mycobacterial infection (7,38,56 (25,35,50). Although M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%